Digital control for interconnected tank system by motor-valve–automatic control (2010)
This paper presents the development and the level control implementation of interconnected tanks system, through a motor-valve as actuator element and a level sensor as a sensor element. The implementation of the digital control is executed by using Matlab through a DAQ of NI. The controllers implemented are PID and algebraical.